TECHNICAL ANALYSIS OF RIGID PAVEMENT AND FLEXIBLE PAVEMENT CALCULATIONS ON TEUKU UMAR ROAD – RAJAWALI ROAD - Budiyanto, Arief; Muhammadun, Haris; Marleno, Risma (Transpublika Publisher, 2024)
Road development in Sampang Regency is carried out based on the Vision and Mission of the 2019-2024 RPJMD, as stated in Mission point 3 Infrastructure: